Navigating development: the case of the non-profit documentary production company STEPS - Carter, Patrice (Department of Sociology, 2017)
Non-governmental organizations (NGOs) in the Global South that work in development are said to operate autonomously from their governments yet their very existence depends largely on dominant bureaucratic bodies - mostly Northern influencers. Indeed, many Southern NGOs are dissatisfied with the sector due to these structural and institutional forces that can be exclusionary, dominating and restricting to their autonomy, affecting the organization's sustainability as leaders within their civil societies. I have ventured to explore how one Southern NGO contends with such an environment. Through conducting an ethnography on Social Transformation and Empowerment Projects (STEPS), a nonprofit documentary production company based in Cape Town, South Africa, I have explored how they navigate within these confines. I have investigated what tacit rules they adhere to in order to remain operational in the sector while also exploring what other rules they attempt to subvert in order to emancipate themselves from these structural forces. This dissertation investigates power struggles in line with Foucault's (1980) theoretical framing on how power exists everywhere and in everything. This study also employs Bourdieu's (1977) concept of habitus and Vigh's (2009) utilization of the concept of navigation as ways to gain a deeper introspection into how these particular practitioners negotiate their positionality within development. Overall, I argue that central to how STEPS navigate the terrain of a contentious development field rest primarily in key decision-makers within the organization. The nature of these practitioners as informed by their life histories has created dispositions that not only inform their agency as individuals but also transfer to their organization (culture, structure, vision, ideologies, ambition). Despite external structures that can also act as roadblocks or allies in actions, choices and agency, the habitus of these prominent figures within the organization are key to actions of the collective when presented with negative or positive structural forces.